O financiamento de projetos de infraestrutura no Brasil: um estudo de 1995 a 2018 - Balistiero, Ricardo (2019)
The main objective of this study is to evaluate, from the reduction of inflation, whether the country's macroeconomic conditions have enabled the emergence of financing sources for infrastructure projects. Some studies focus on shorter time periods, hindering the understanding of economic and political cycles and their effects on the emergence of funding sources for this sector. The theoretical part is elaborated from the conceptualization of the infrastructure sector as market failure, as well as the importance of institutions, government failures and the main forms of financing of sector projects. The context of the Brazilian economy in the period makes it possible to understand the main changes in macroeconomic management. Data collection included interviews with various professionals involved with the sector, as well as the compilation of texts in the press and through the “Lei de Acesso à Informação”. The results show that the public sector was the main provider of resources for the sector, through budget and through public banks. As the fiscal crisis worsened, more market-oriented and private-sector operations became part of the options for financing the sector, with the limitations imposed by political cycles and constant changes in economic policy. Actions to minimize the risks posed to potential participants in this market, based on a scenario of rapid and constant changes, influence the attraction of new stakeholders in financing infrastructure projects in the country.